ANALISA IRIGASI PERSAWAHAN DI DAERAH ALIRAN SUNGAI SILUGONGGO - Kukuh Wisnuaji Widiatmoko (Rang Teknik Journal, 2026)
The Silugonggo River is located in Pati Regency, Central Java, this river is included in the Juwana Watershed Area. Most of the residents around the Silugonggo river work as farmers, where every dry season they are faced with a lack of water which results in a decrease in crop yields. Based on the existing problems, an optimization study was carried out on effective planting schedules and patterns in the surrounding area.The area of the irrigation area is determined to be 12 km long, with a radius of 1.5 km on the right and left sides of the river, with an area of 4,891 Ha. The methodology used, including Hydrological Analysis, includes calculating regional average rainfall (Thissen Polygon), effective rainfall (Weibull Probability), Maximum rainfall, mainstay discharge (Weibull), climatological analysis using Evapotranspiration (Modified Penmann), and Percolation, then carried out Analyze water requirements for plants and determine planting pattern schedules. The results of the calculations show that the schedule and planting pattern for Alternative I starts on November 1, because the amount of water required is less than the other alternatives. There are several months where water availability is not able to meet the water needs of the entire DI, this occurs in August II, September I and II.